New records of ribbon worms (Nemertea) from Ceará, Northeast Brazil - Mendes, Cecili B.; Matthews-Cascon, Helena; Norenburg, Jon L. (Zootaxa, 2016)
Of 45 species of nemerteans reported for the Brazilian coast, only two were recorded from Brazil’s Northeast coast. Here we report seven new records for the state of Ceará, in Northeast Brazil: Tubulanus rhabdotus Côrrea, 1954, Carinomella cf. lactea Coe, 1905, Baseodiscus delineatus (Delle-Chiaje 1825), Cerebratulus cf. lineolatus Coe, 1905, Cerebratulus sp. 1, Cerebratulus sp. 2 and Lineidae sp. 1. Specimens were collected at the following beaches: Praia dos Dois Coqueiros, Praia do Pacheco, Pecém harbor, Praia da Pedra Rachada and Praia do Guajiru. T. rhabdotus is a new record for Northeast Brazil, Carinomella cf. lactea and Cerebratulus cf. lineolatus are new records for the South Atlantic Ocean and both genera are new records for Brazil.